Reproductive capacity and recurrence of disease after surgery for moderate and severe endometriosis - a retrospective single center analysis - Cordula Schippert; Yvonne Witte; Janina Bartels; Guillermo-José; Matthias Jentschke; Peter Hillemanns; Sudip Kundu (BMC, 2020)
Abstract Background Endometriosis can be associated with considerable pain and sterility. After surgical excision of moderate or severe endometriosis lesions, the rate of recurrence reaches up to 67%. The objective of this retrospective study was to establish the recurrence and pregnancy rates following surgical resection of stage III/IV endometriosis lesions. Indications for operation were endometriosis symptoms, sonographic findings and/or infertility. Methods A total of 456 patients who underwent stage III/IV endometriosis surgery between 2004 and 2014 were sent a questionnaire relating to their postoperative medical treatment, pregnancies, relief of symptoms and recurrence. Responses of 206 patients (45.2%) and their clinical data were analysed for this study. Results A total of 66.5% (N = 137) of patients had stage III disease, and 33.5% (N = 69) had stage IV disease. The average age was 37 years (17-59). A total of 63.1% (N = 130) of surgeries were performed by laparoscopy, 21.8% (N = 45) were performed by laparotomy and 15% (N = 31) were performed by conversion. Complete resection of endometriosis lesions was achieved in 90.8% of patients (N = 187). After surgery, 48.5% (N = 100) of the women did not receive hormonal treatment; the main reason was the desire for children in 53%. Complete or partial relief in complaints was achieved in 93.2% (N = 192). The rate of recurrence was 21.8% (N = 45). The statistically significant factors that was associated with a higher risk to develop recurrence was an age < 35 (p < 0.005). After surgery, 65.8% (79/120) of patients who wished to have children became pregnant. There was a statistically significant association among a higher postoperative pregnancy rate and age < 35 (p < 0.003) in multivariate logistic regression analysis and laparoscopic surgical access in univariate logistic regression analysis (p < 0.01). Conclusion We assessed the high percentage of complete or partial relief of symptoms of 93.2%, the high postoperative pregnancy rate of 65.8% and the low rate of recurrence of 21.8% compared to international literature to be very encouraging for women suffering from moderate and severe endometriosis. Though laparoscopy is considered the 'gold standard'of endometriosis surgery, laparotomy still may be indicated in patients with extensive endometriosis especially to preserve reproductive function.